Light adaptation mechanisms in the eye of the fiddler crab Afruca tangeri. Issue 3 (6th July 2020) - Brodrick, Emelie A.; Roberts, Nicholas W.; Sumner‐Rooney, Lauren; Schlepütz, Christian M.; How, Martin J.
Abstract: A great diversity of adaptations is found among animals with compound eyes and even closely related taxa can show variation in their light‐adaptation strategies. A prime example of a visual system evolved to function in specific light environments is the fiddler crab, used widely as a model to research aspects of crustacean vision and neural pathways. However, questions remain regarding how their eyes respond to the changes in brightness spanning many orders of magnitude, associated with their habitat and ecology. The fiddler crab Afruca tangeri forages at low tide on tropical and semi‐tropical mudflats, under bright sunlight and on moonless nights, suggesting that their eyes undergo effective light adaptation. Using synchrotron X‐ray tomography, light and transmission electron microscopy and in vivo ophthalmoscopy, we describe the ultrastructural changes in the eye between day and night. Dark adaptation at dusk triggered extensive widening of the rhabdoms and crystalline cone tips. This doubled the ommatidial acceptance angles and increased microvillar surface area for light capture in the rhabdom, theoretically boosting optical sensitivity 7.4 times. During daytime, only partial dark‐adaptation was achieved and rhabdoms remained narrow, indicating strong circadian control on the process. Bright light did not evoke changes in screening pigment distributions, suggesting a structural inability to adapt rapidly to the light level fluctuations frequently experienced when entering their burrow to escape predators. This should enable fiddler crabs to shelter for several minutes without undergoing significant dark‐adaptation, their vision remaining effectively adapted for predator detection when surfacing again in bright light. Abstract : Dark‐adapting the fiddler crab eye at night triggers great changes in rhabdom diameters and crystalline cone shape, increasing optical sensitivity and acceptance angles. However, during daytime the eye remains effectively light‐adapted in the dark. Surprisingly, screening pigments do not appear to migrate to help moderate fluctuations in brightness.